Barriers to Lose Weight from the Perspective of Children with Overweight/Obesity and Their Parents: A Sociocultural Approach - Ana Lilia Rodríguez-Ventura; Ingris Pelaez-Ballestas; Reyna Sámano-Sámano; Carlos Jimenez-Gutierrez; Carlos Aguilar-Salinas (Journal of Obesity)
Introduction. There are not enough studies about the barriers to lose weight from the perspective of children and their parents. Methods. Children and adolescents diagnosed with overweight/obesity in the Department of Endocrinology and their parents were invited to participate in a series of focus group discussions (FGD). Twenty-nine children 10–16 years old and 22 parents participated in 7 focus groups; 2 mothers and 2 adolescents participated in depth interviews. All interviews were recorded, transcribed, and analyzed through grounded theory. Results. Parents went to the hospital only when their children presented any obesity complication; for them, overweight was not a health problem. Parents referred to lack of time to supervise about a healthy diet and exercise; besides, the same parents, relatives, friends, and the mass media encourage the consumption of junk food. Children accepted eating a lot, not doing exercise, skipping meals, and not understanding overweight consequences. Both, parents and children, demanded support to do the time recommended for exercise inside the schools. They also suggested getting information from schools and mass media (TV) about overweight consequences, exercise, and healthy food by health workers; they recommended prohibiting announcements about junk food and its sale. Conclusions. The barriers detected were lack of perception of being overweight, its identification as a disease and its consequences, lack of time to supervise a healthy lifestyle, and a big social influence to eat junk food.